The Impact of Experimental Methods Using Hydroponic Techniques on Student Learning Outcomes in Primary School Science Education - Anis, Moh. Badiul; Azizah, Noor; Rukayah, Rukayah (Yayasan Darussalam Bengkulu, 2024)
This study investigates the effectiveness of the experimental method, specifically using hydroponic techniques, in improving student learning outcomes in primary school science education. A quasi-experimental design with pre-test and post-test measures was employed, involving two groups of sixth-grade students from MI NU Tamrinut Thullab Undaan Kudus, Indonesia. The experimental group engaged in hands-on hydroponic activities, while the control group received traditional lecture-based instruction. The results indicate a significant improvement in the experimental group’s post-test scores (M = 89.31) compared to the control group (M = 74.33), with statistical analysis revealing a t-value of 5.85 (p < 0.05). Qualitative feedback from students further supports these findings, as they reported increased motivation and a deeper understanding of scientific concepts through the experimental method. This study highlights the potential of inquiry-based, hands-on learning to enhance student engagement and performance, especially in resource-limited educational settings. The findings suggest that integrating experimental methods into the science curriculum can significantly improve learning outcomes and should be considered in future educational reforms. However, the study's limitations, including a small sample size, indicate the need for further research to replicate these findings in diverse contexts.